PENGARUH KARAKTERISTIK PERUSAHAAN DAN UKURAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Mukti, Achmad; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of profitability, profile, firm size, leverage and the size of board of of commissioner to the disclosure of corporate social responsibility. The results of this study show that: (1) profitability has positive influence to the corporate social responsibility, (2) profile has positive influence to the corporate social responsibility, (3) firm size has positive influence to the corporate social responsibility, (4) leverage has negative influence to the corporate social responsibility, and (5) the size of board of commisioner has negative influence to the corporate social responsibility.Keywords: profitability, profile, firm size, leverage and size of board of commisioner